Metodologia y progreso de los proyectos de investigacion en sistemas agricolas del ICA en Colombia - Urrego M., G. (International Center for Tropical Agriculture, 1987)
The purpose of the ICA research project on agricultural systems in Colombia is to generate appropriate technology for the different conditions of the growers and the area as well as plan research and technology transfer. The methodology used is described. Currently, the project is being carried out in 2 areas; one with small and medium-size growers at the plateau region of Narino and the dale of the Suarez and Chicamocha rivers, and another with large-scale growers at the savanna in Bogota. Some recommendations are mentioned. (CIAT)